ACTIVITY OF LIVER FUNCTION ENZYME AND ANTIBACTERIAL SUSCEPTIBILITY OF ANNONA SENEGALENSIS LEAF EXTRACT - JUDE, JEGEDE ROTIMI; JOHN, OGUNBIYI OLUWAGBENGA; JUMMAI, ALAO VICTORY (Innovare Journal of Life Sciences, 2023)
In ethnomedicine, various natural products have been implicated in the treatment of several diseases. Annona senegalensis has been identified as one of the plants that have the potential to cure ailments arising from microbial infections. This study however was carried out to investigate the liver function enzyme activity and in vitro antibacterial susceptibility of the 50% ethanol-methanol leaf extract of A. senegalensis. The effect of the administration of 100 mg/kg body weight of A. senegalensis on serum enzyme parameters and antibacterial susceptibility was investigated in albino rats. Thirty-three albino rats with average weights of 200 g were divided into two groups. Group 1 contained 30 rats and was treated with 20 mg/mL of A. senegalensis leaf extract while Group 2 contained three rats and served as the control. The treatment lasted for 20 consecutive days while the rats in Group 1 were daily administered with the leaf extract of A. senegalensis. Data were analyzed and presented using a descriptive analysis from Microsoft Excel 2016 version. The results obtained from administration of the leaf extract of A. senegalensis on serum enzymes parameters show a significant increase in serum enzyme activity when compared to the control. This indicates that the leaf extracts of A. senegalensis have significant effects on the serum enzymes parameters. The in vitro antibacterial susceptibility of the leaf extracts relative to the drugs (Ampicillin and Ciprofloxacin) revealed that the leaf extract of the plant holds much promise in antibacterial property when combined with antibiotics used in this study. This research revealed that there is high activity of alkaline phosphatase, aspartate aminotransferase, and alanine aminotransferase in the serum following the administration of 100 mg/kg body weight of 50% ethanol-methanol leaf extract of A. senegalensis. The antibacterial susceptibility test of the leaf extract carried out in vitro also revealed the plant antibacterial property. The combination of A. senegalensis leaf extract with antibiotic drugs, especially the one used in this study hold much promise in its efficacy as revealed in its synergistic interaction.